PERAN TEKNOLOGI INFORMASI DALAM PENDIDIKAN ISLAM DI TENGAH PANDEMI COVID-19 - Pangestu, Wilis Hariani; Abidin, Zaenal (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
Science and technology that has developed continuously bring changes in human life since the end of the 20th century. Humans must be able to master the times so that they can lead science and technology in the next century. Islam views science and science and technology as important. The era of the Islamic industrial revolution pays attention so that the advancement of educational technology is richer in knowledge. How did Muslims and Indonesia use information technology in education during the Covid-19 pandemicHis research is a qualitative research type of literature research. This type of data collection is a study of descriptive data analysis documents. The focus of research is the development of Islamic technology and the importance of communication technology in the technological era like today.The development of developing technology also helps and makes it easier for people to do their activities. One of the perceived conveniences is the ease of communicating and obtaining information online at a cost that is not too expensive. Since the emergence of the Covid-19 outbreak in Indonesia, learning in schools has stopped. During the Covid-19 pandemic, which advocates at home, the role of communication media is needed to continue learning